2014
DOI: 10.4103/0257-7941.147422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic effects of Anbarnesa on fibroblast L929: Can it be used as a mouthwash?

Abstract: Aims:In Iranian traditional medicine Anbarnesa (derived from smoke from burning female donkey's stool) has been used to treat ulcers and inflammatory conditions like stomatitis and ear infections (otitis). We assess the properties of Anbarnesa as an alternative mouthwash.Materials and Methods:In this experimental study, Anbarnesa smoke was analyzed using aGC-mass device. The smoke collected was dissolved at different densities in propylene glycol and incubated in Dulbecco's modified Eagle's medium in direct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A literature search using the above-mentioned criteria yielded a total of 4 articles on anbarnesa smoke ( 4 , 5 , 10 , 11 ). All articles had been conducted by the Iranian researchers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A literature search using the above-mentioned criteria yielded a total of 4 articles on anbarnesa smoke ( 4 , 5 , 10 , 11 ). All articles had been conducted by the Iranian researchers.…”
Section: Resultsmentioning
confidence: 99%
“…All articles had been conducted by the Iranian researchers. Two articles were in English ( 4 , 5 ) and 2 in Farsi ( 10 , 11 ). Detailed findings are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Some studies have been recently conducted on the cytotoxic activity of Anbarnasara. While Shafiee et al claimed that its smoke has no cytotoxic activity on L929 cell line, 17 Sadeghi-Aliabadi et al reported cytotoxic activity of this smoke not only on L929 (which is a normal cell) but also on immortal cancerous cells of HeLa and KB. 18 This contradiction could also be related to different sources of supplying or different time of collecting Anbarnasara, or even different grass eaten by donkeys.…”
Section: Discussionmentioning
confidence: 99%